Effect of pH on Physicochemical Properties and Encapsulation Efficiency of PEGylated Linolenic Acid Vesicles - Yin Yin Teo; Misni Misran; Kah Hin Low (E-Journal of Chemistry)
The preparation of vesicle from a mixture of linolenic acid and 1,2-dipalmitoyl-sn-glycerol-3-phosphoethanolamine-N-[methoxy-(polyethylene glycol) -2000] (DPPE-PEG2000) has been successfully carried out by using dry lipid hydration method. The effect of pH on particle size, zeta potential, encapsulation efficiency and critical vesiculation concentration (CVC) of the prepared vesicle suspensions in aqueous were studied. Macroscopic stability of the vesicles was also evaluated through their particle size and zeta potential for a period of 30 days. We found that CVC vary according to the pH, with higher pH of the bulk solution, CVC is higher. Vesicles formed at pH 8.5 were the most stable suspension throughout a period of 30 days compared to those at pH 7.5 and pH 9.0. Addition of DPPE-PEG2000 into the preparation of vesicle at pH 8.5 caused a reduction of the vesicle size to the scale of nanometer which is an advantage to their application. On the other hand, encapsulation of calcein and vitamin E were carried out. Certain amount of these compounds could be successfully loaded into the resulting liposomes under this experimental condition.